A deletion of IDUA exon 10 in a family of Golden Retriever dogs with an attenuated form of mucopolysaccharidosis type I. (12th August 2020) - Faller, Kiterie M. E.; Ridyard, Alison E.; Gutierrez‐Quintana, Rodrigo; Rupp, Angie; Kun‐Rodrigues, Celia; Orme, Tatiana; Tylee, Karen L.; Church, Heather J.; Guerreiro, Rita; Bras, Jose
Abstract: Background: Mucopolysaccharidosis type I (MPS‐I) is a lysosomal storage disorder caused by a deficiency of the enzyme α‐l ‐iduronidase, leading to accumulation of undegraded dermatan and heparan sulfates in the cells and secondary multiorgan dysfunction. In humans, depending upon the nature of the underlying mutation(s) in the IDUA gene, the condition presents with a spectrum of clinical severity. Objectives: To characterize the clinical and biochemical phenotypes, and the genotype of a family of Golden Retriever dogs. Animals: Two affected siblings and 11 related dogs. Methods: Family study. Urine metabolic screening and leucocyte lysosomal enzyme activity assays were performed for biochemical characterization. Whole genome sequencing was used to identify the causal mutation. Results: The clinical signs shown by the proband resemble the human attenuated form of the disease, with a dysmorphic appearance, musculoskeletal, ocular and cardiac defects, and survival to adulthood. Urinary metabolic studies identified high levels of dermatan sulfate, heparan sulfate, and heparin. Lysosomal enzyme activities demonstrated deficiency in α‐l ‐iduronidase activity in leucocytes. Genome sequencing revealed a novel homozygous deletion of 287 bp resulting in full deletion of exon 10 of the IDUA gene (NC_006585.3(NM_001313883.1):c.1400‐76_1521+89del). Treatment with pentosan polyphosphate improved the clinical signs until euthanasia at 4.5 years. Conclusion and Clinical Importance: Analysis of the genotype/phenotype correlation in this dog family suggests that dogs with MPS‐I could have a less severe phenotype than humans, even in the presence of severe mutations. Treatment with pentosan polyphosphate should be considered in dogs with MPS‐I.